Hemimyzon yushanensis, a new species of balitorid fish (Teleostei: Baltiordae) from southern Taiwan - Chen, I-Shiung; Harefa, Tonisman; Chang, Yung-Ching; Han, Chiao-Chuan (Zootaxa, 2022)
The new balitorid fish was collected in the Kaoping river basin from southern Taiwan. The new balitorid, Hemimyzon yushanensis n. sp. can be well distinguished from other congeneric species by following combination of features: (1) dorsal fin rays 3 + 8; pectoral fin rays 11-13 + 9-11 (total 22-23; modally 22); (2) lateral-line scales 69-72 (modally 70); predorsal scales 25-30 (26-27); (3) pelvic fin moderate large, extending to rear vertical of dorsal fin; (4) the position of anus with larger distance of pelvic rear tip to anus about 1.2-1.7 times of that of anus to anal fin origin; and (5) specific coloration: predrorsal region and head with rounded creamy yellow spots, pectoral and pelvic fins with several small whitish spots on greenish brown background. The morphological comparison of congeners and diagnostic key of Taiwanese species would be also provided in this paper.